Reproduction Method of Rockfall Geologic Hazards Based on Oblique Photography and Three-Dimensional Discontinuous Deformation Analysis - Fu, Xiaodong; Ding, Haifeng; Sheng, Qian; Chen, Jian; Chen, He; Li, Guo; Fang, Liuyang; Du, Wenjie (Frontiers in Earth Science, 2021)
Rockfall geologic hazards are widely distributed. Due to their concealed nature, the rockfalls are difficult to be effectively investigates using the traditional contact survey method, and the hazards seriously affect major projects and people's safety. Reproducing methods including scene survey and movement process analysis are the primary tasks to prevent the hazards. However, few reconstruction methods can directly apply the parameters of the rockfall geologic hazards obtained by scene survey to analysis the movement process. To break through this problem, a reproduction method based on oblique photography and three-dimensional discontinuous deformation analysis (3D-DDA) is presented in this paper, and this method is consist of three key technologies, including oblique photography, 3D rock block system modeling and 3D rock block system analysis. Firstly, geometric characteristic parameters of the terrain, rockfall and discontinuities are extracted based on oblique photography using unmanned aerial vehicle (UAV). Secondly, taking these geometric characteristic parameters as input, the block system model of rockfall is reconstructed by using 3D computational geometry theory. Finally, the whole evolution processes of rockfall geologic hazard, including initiation, movement and accumulation, are simulated by the 3D-DDA method. To test the practicability of this reproduction method, a typical rockfall geologic hazard, located in K8 + 050 section of Gaohai expressway, Yunnan, China, is studied. Based on oblique photography using UAV, the characteristics of 19 dangerous rock masses in the survey area are clarified, and the geometric features of the discontinuities in the rock masses are extracted. The block system model of a potential rockfall is reconstructed, the movement trajectory is simulated by 3D- DDA method, and the evolution process of velocity and kinetic energy of the rockfall verifies that the spatial layout of the current three-level passive protective nets system is reasonable. The case study shows that the proposed method can provide a geological and mechanical model for the risk assessment of rockfall geologic hazards.